1990
DOI: 10.1007/bf00453137
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin, estradiol, and hydroxyproline as parameters in the early diagnosis of involutional osteoporosis

Abstract: Bone metabolism was studied in a group of 92 subjects. A greater age-related decrease in calcitonin and estradiol concentrations exists in women than in men, though this difference was not significant; it was significant, however, when the values of the three different groups of women were compared. We present what we have called the second calcitonin phenomenon, that is, a highly significant difference in women between a second basal calcitonin level and the primary admission value. In the calcium infusion te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Some research suggested that increased serum and urine levels of hydroxyproline had been demonstrated in Paget’s disease bone [52], [53]. Meanwhile, mean plasma levels of branched-chain amino acids (BCAA, leucine, isoleucine, and valine) raised rapidly in the first three week after OVX and remained significantly elevated (p<0.05 versus sham-operated controls) for the entire 24 week.…”
Section: Discussionmentioning
confidence: 99%
“…Some research suggested that increased serum and urine levels of hydroxyproline had been demonstrated in Paget’s disease bone [52], [53]. Meanwhile, mean plasma levels of branched-chain amino acids (BCAA, leucine, isoleucine, and valine) raised rapidly in the first three week after OVX and remained significantly elevated (p<0.05 versus sham-operated controls) for the entire 24 week.…”
Section: Discussionmentioning
confidence: 99%